Diseño, implementación y puesta en servicio de un sistema de radio troncalizado digital de misión crítica para Minera Las Bambas - Álamo Rodríguez, Marcos Alexander (2018)
This article analyzes the management of a telecommunications project to comply with the main deliverables of: design, procurement, civil works and the commissioning of a trunked radio system, complying with the requirements and standards of the client, applying the experience technical, good management practices and subsidiary plans of scope, cost, time, quality, human resources, communications, stakeholders, acquisitions, risks and integration, which for the project are aligned to meet the critical success factor of delivering the project before of the requested time. As main results we obtained the work breakdown structure (WBS), the schedule with 14 calendar months, a budget of around US $ 6 million, response plans for negative risks and contingency reserve, communication matrix, RACI matrix, control activities and quality assurance, selection of suppliers and finally the integration of all these plans.